Preliminary ReportsComparison of the GTV coverage by PTV and isodose of 90% in 2D and 3D planning during endobronchial brachytherapy in the palliative treatment of patients with advanced lung cancer. Pilot study - Łyczek, Jarosław; Kazalski, Damian; Kowalik, Łukasz; Sawicki, Marcin (Journal of Contemporary Brachytherapy, 2012)
Purpose : Endobronchial brachytherapy (EB) is one way of treatment of patients with advanced lung cancer. Technological progress and the introduction of computed tomography for use in 3D planning allows one to define the area being treated very precisely, which gives an opportunity to extend survival, even in groups of patients receiving palliative care. Material and methods : In 2011, in the Brachytherapy Department of the Subcarpathian Oncological Center, a group of 12 consecutive patients with advanced cancer of the bronchus underwent palliative EB. We compared the coverage of GTV (gross tumor volume), seen in the computed tomography study with intravenous contrast, by the PTV (planning target volume) planned in 3D and 2D. Results: In 2D planning GTV coverage ranged from 15% to 89%. By analyzing the isodose of 90%, it was found that 2D planning covered GTV in 15-35% of the dose. In 3D planning, this coverage changed positively, and ranged from 85% to 100%. The GTV coverage in 3D planning was 100% by definition. In addition, it should be noted that in the 3D planning one can spare critical organs or pacemakers. Conclusions : Planning for HDR brachytherapy in all locations should be based on dynamic imaging at present, especially in centers that are equipped with CT. Evaluation should be a routine test in treatment planning. The use of CT, even in palliative treatment planning, allows for much better coverage of GTV areas as well, which is very important to reduce radiation doses to critical organs and thereby reduce the toxic effects of treatment.